PERBAIKAN KUALITAS AIR DENGAN SISTEM PENYARINGAN DI PENAMBANGAN RAKYAT INTAN DAN EMAS DI KECAMATAN CEMPAKA KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Tyas Astari; Emmy Sri Mahreda; Danang Biyatmoko; Gusti Chairuddin (EnviroScienteae, 2013)
Writing of this thesis is motivated by the declining water quality in rivers around the mining area due to mining of the people that do not meet clean water requirements. Purpose of this study was to determine the influence of the filtering system of physical and chemical water quality in the watershed are derived from the people of the diamond and gold mining areas as well as the assessment of water quality in producing water that meets the requirements of clean water in accordance with the requirements of Health Minister of Republic (PerMenKes RI) No. 416/MenKes/Per/IX/90. The research method used was semi-experimental. What matters is whether a particular filtering technology can improve the quality of river water and can produce better water quality?. The results showed that there is a difference between before filtering with post filtering (sand filter and activated charcoal filter). By the two different filters (sand and activated charcoal), the finest and most effective sand filters in the improvement of physical and chemical quality of water. Sand filter has a high effectiveness of the reduction. By the ten parameters of the observed parameters of TSS, turbidity and reduction of Fe which has a high effectiveness. The results can be concluded that the filtration systems (sand filter and activated charcoal filter) affects the physical and chemical quality of water. Filtering results with a sand filter and activated charcoal filters have improved physical and chemical quality of water that clean water has been qualified in accordance with the requirements of Health Minister of Republic (PerMenKes RI) No. 416/MenKes/Per/1990.